Dialektika Spiritualitas dan Profesionalisme dalam Manajemen Sumber Daya Manusia - Debi Tiara Wulan Dari; Zainal Berlian; Baharudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study reconstructs the conceptual relationship between modern professionalism in human resource management (HRM) and Islamic spirituality within an integrative framework. Mainstream HRM literature predominantly conceptualizes professionalism as a rational-instrumental system grounded in competency, performance metrics, and strategic alignment, often presuming value neutrality. In contrast, Islamic management emphasizes tawhid, amanah, and ihsan as ethical foundations of work, yet lacks systematic operational integration into contemporary HRM models. Employing a qualitative approach through a systematic literature review of international publications (2020-2024), this study conducts a critical-conceptual synthesis to address this theoretical gap. The findings demonstrate that the perceived dichotomy between professionalism and spirituality can be reconciled through a value-based HRM paradigm integrating structural accountability with spiritually grounded moral responsibility. The study contributes theoretically by redefining professionalism as inherently value-embedded, offering a holistic and ethically grounded alternative for contemporary HRM theory and practice.